État nutritionnel et environnement pathogène d’enfants d’une population forestière du Sud-Cameroun - Olivier Bernard; Hélène Pagezy; Daniel Bley (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Growth in height and weight is considered as indicators of nutritional status; they respond to both genetic and environmental factors such as nutritional value of the diet, exposition to infectious and parasitic diseases, sociocultural and psychoaffective context. This study concerns the relationship between splenomegaly as an indicator of a chronic context of parasitic load and the growth in height or weight of preschool children from rainforest Southern Cameroon. The anthropometric study shows that 31,6% of the 0-6 years old children are stunded and 3,6% wasted. The height retardation follows the evolution of the spenomegaly. The results are in accordance with the importance of infectious factors, especially paludism in the installation and the perenniality of a chronic malnutrition status.